2012
DOI: 10.1002/job.1790
|View full text |Cite
|
Sign up to set email alerts
|

I can't get no job satisfaction: Meta‐analysis comparing permanent and contingent workers

Abstract: Summary Scholars are concerned that contingent workers experience more adverse psychological job outcomes than permanent employees, but the empirical work on job satisfaction is mixed. The purpose of this study was to quantitatively summarize the potential mean differences in job satisfaction between contingent workers and permanent employees. Meta‐analytic results from 72 primary studies (N = 237 856) suggest that compared with permanent employees, contingent workers experience lower job satisfaction (d = −0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 81 publications
5
112
2
6
Order By: Relevance
“…Wilkin (2013) shows in a meta-study that job satisfaction is significantly lower among temporary agency workers than among permanent workers and temporary employees. One important explanation for lower job satisfaction among temporary agency workers is the lack of job security.…”
Section: Previous Research and Theoretical Frameworkmentioning
confidence: 99%
“…Wilkin (2013) shows in a meta-study that job satisfaction is significantly lower among temporary agency workers than among permanent workers and temporary employees. One important explanation for lower job satisfaction among temporary agency workers is the lack of job security.…”
Section: Previous Research and Theoretical Frameworkmentioning
confidence: 99%
“…An important one is the level of the job: a skill mismatch negatively influences job satisfaction (Allen and van der Velden 2001;Mavromaras et al 2010). The type of employment also plays a role: in a metaanalysis Wilkin (2013) showed that non-permanent employment decreases job satisfaction. The type of non-permanent employment matters: self-employed persons are as satisfied as permanent employees, whereas agency workers and direct-hires (i.e., persons hired on a temporary contract directly by the company) are less satisfied.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Wilkin (2012) used studies from across the globe gaining access to key studies in the area. Her research found that contingent workers experience lower job satisfaction than permanent workers although she commented that the difference was small although significant.…”
Section: Job Satisfactionmentioning
confidence: 99%